Collaborative training of regulators as an approach for strengthening regulatory systems in LMICs: experiences of the WHO and Swissmedic - Dehaghi, Razieh Ostad Ali; Khadem Broojerdi, Alireza; Paganini, Lodovico; Sillo, Hiiti B. (Frontiers in Medicine, 2023)
Introduction Training opportunities for health product regulators are among the critical aspects in the strengthening of regulatory systems across the world. The need for training is reasonably higher among the National Regulatory Agencies (NRAs) in the Low- and Middle-Income countries (LMICs) which are faced with many regulatory challenges mostly rooted in the low availability of resources. The current study aimed at evaluating the suitability, impacts, and challenges related to the training of regulators from LMICs offered by the Swissmedic in collaboration with the World Health Organization (WHO). Methodology An exploratory case study design using a qualitative approach was adopted to collect data from a total of 17 NRAs in different WHO regions using in-depth interviews and qualitative questionnaires. Results The participation of the trainees in the training was revealed to be motivated by the need to apply the obtained knowledge in addressing various challenges within their NRAs. Many lessons covering all key areas of health products regulation were reported by the trainees, whereby most of the lessons were already being implemented within their respective NRAs. However, challenges related to human, financial, and infrastructural resources were highlighted to hinder the ongoing efforts in putting the learned aspects into practice. Additionally, areas in which further regulatory assistance and suggestions for improving the training activities were pointed out. Conclusion The highlighted gains from the WHO-Swissmedic collaborative training program call for other agencies and organizations to join hands in offering much-needed support towards addressing critical challenges facing the regulatory sector in the LMICs.